2010
DOI: 10.1016/j.ejps.2010.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic screening of soluble epoxide hydrolase inhibitors in dogs

Abstract: Epoxyeicosatrienoic acids that have anti-hypertensive and anti-inflammatory properties are mainly metabolized by soluble epoxide hydrolase (sEH, EC 3.3.2.3). Therefore, sEH has emerged as a therapeutic target for treating various cardiovascular diseases and inflammatory pain. N,N’-Disubstituted ureas are potent sEH inhibitors in vitro. However, in vivo usage of early sEH inhibitors has been limited by their low bioavailability and poor physiochemical properties. Therefore, a group of highly potent compounds wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(150 citation statements)
references
References 58 publications
5
145
0
Order By: Relevance
“…1, A and B). TPPU is a highly selective inhibitor of sEH with an IC 50 of 1.1 and 2.1 nM for murine and human sEH, respectively (Rose et al, 2010;Tsai et al, 2010;Liu et al, 2013). We previously demonstrated that sEH pharmacological inhibition does not alter sEH protein expression, and that prolonged sEH inhibition in mice appears to be quite benign (Luria et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…1, A and B). TPPU is a highly selective inhibitor of sEH with an IC 50 of 1.1 and 2.1 nM for murine and human sEH, respectively (Rose et al, 2010;Tsai et al, 2010;Liu et al, 2013). We previously demonstrated that sEH pharmacological inhibition does not alter sEH protein expression, and that prolonged sEH inhibition in mice appears to be quite benign (Luria et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, by the time one could isolate the sEH enzyme, the inhibitor would have diffused away from the catalytic site; however, the 10 mg/ kg/day dose used in this study results in blood levels above the IC 50 for t-TUCB, and t-TUCB increases the ratio of epoxides to diols for several oxylipin chemical mediators and reduces infl ammatory cytokines in the plasma even at 3 mg/kg in mice. These plasma epoxide-to-diol ratios have been demonstrated to be dose-related indicators of in vivo sEH target engagement in a number of species, including mice ( 57-59 ), rats ( 60,61 ), dogs ( 62 ), and monkeys ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 14,15-, 11,12-EET or vehicle were administered intraperitoneally via osmotic minipump (Alzet) at a dose of 15 μg·kg −1 ·d −1 . TUPS was synthesized as described (24,25), and TUPS was completely dissolved in PEG 400 at a concentration of 10 mg/mL and mixed into Vanicream to obtain a 0.1% (wt:vol) formulated cream. The sEHi (TUPS) was administered orally by gavage in an aqueous solution of 10% (vol/vol) DMSO in 0.5% methylcellulose (10 mg·kg −1 ·d −1 ) or as a 0.1% cream applied topically; control mice received vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…We first studied compounds that increase EETs by inhibiting sEH, the main metabolizing enzyme of EETs. Notably, several structurally distinct sEH inhibitors (sEHis) are being evaluated for clinical indications (3,24,25). Systemic administration of the sEHi 1-(1-methylsulfonyl-piperidin-4-yl)-3-(4-trifluoromethoxy-phenyl)-urea (TUPS, UC1709) increased liver regeneration by 38% compared with vehicle-treated mice (Fig.…”
Section: Pharmacological Manipulation Of Eets and Their Action In Organmentioning
confidence: 99%